The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11356-017-8830-y
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of 25 pharmaceuticals in Taihu Lake and their removal from two urban drinking water treatment plants and a constructed wetland

Abstract: Pharmaceuticals in drinking water sources have raised significant concerns due to their persistent input and potential human health risks. The seasonal occurrence of 25 pharmaceuticals including 23 antibiotics, paracetamol (PAR), and carbamazepine (CMZ) in Taihu Lake was investigated; meanwhile, the distribution and removal of these pharmaceuticals in two drinking water treatment plants (DWTPs) and a constructed wetland were evaluated. A high detection frequency (>70%) in the Taihu Lake was observed for nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…For the spatial distribution, as a whole, the EDC concentrations in Wuxi Taihu Lake (North Taihu Lake, S1-S5) is higher than that in the Suzhou Taihu Lake (East Taihu Lake, S6-S9), which is consistent with our previous drug research results [36]. The concentration of EDCs in different spatial sampling points also varied greatly, which may be caused by the different hydrological conditions of the lake water in different periods.…”
Section: Seasonal Variation and Spatial Distributionsupporting
confidence: 89%
“…For the spatial distribution, as a whole, the EDC concentrations in Wuxi Taihu Lake (North Taihu Lake, S1-S5) is higher than that in the Suzhou Taihu Lake (East Taihu Lake, S6-S9), which is consistent with our previous drug research results [36]. The concentration of EDCs in different spatial sampling points also varied greatly, which may be caused by the different hydrological conditions of the lake water in different periods.…”
Section: Seasonal Variation and Spatial Distributionsupporting
confidence: 89%
“…High OTC concentrations (>50 ng L -1 ) were found in Taihu Lake (Xu et al 2014), Baiyangdian Lake (Cheng et al 2014;Cheng et al 2017) and Honghu Lake (Wang et al 2017c). High CTC concentrations were found in the bulk water of Taihu Lake with different sampling times from May 2010 to December 2015 (Hu et al 2017a;Xu et al 2014;Zhou et al 2016) and Honghu Lake (Wang et al 2017c).…”
Section: Tetracyclinesmentioning
confidence: 95%
“…Besides the high levels accounted for acetylsalicylic acid and acetaminophen in surface waters from the region of São Paulo, it is important to mention that these pharmaceuticals were not frequently detected in the samples, probably due to changes in the quantification limits of the methods over the years. Hu et al 60 investigated the occurrence of 25 pharmaceuticals in a Chinese lake and observed average concentrations varying between 45 and 58 ng L -1 , depending on the season of the sampling. Tewari et al 61 reported acetaminophen concentrations from 44 to 435 ng L -1 in six discharge canals of the Chao Phraya River, in Thailand as well as concentrations up to 70 ng L -1 in the receiving waters.…”
Section: Pharmaceuticals and Personal Care Productsmentioning
confidence: 99%